2007
DOI: 10.22230/cjc.2007v32n3a1866
|View full text |Cite
|
Sign up to set email alerts
|

Rose-Coloured Glasses: The Discourse on Information Technology in the Romanow Report

Abstract: Here discourse about information technology in Canada’s health sector is examined. After an overview of the emergence of the Canadian Health Information Infrastructure, discourse within the Romanow Report is discussed in relation to three key themes: standardization, empowerment, and time/space compression. While an instrumental view of technology in the health care sector is the predominant discourse articulated in the report, we argue that, by emphasizing technology assessment, the Romanow Report makes room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“……You smarten up and gain control" (Interviewee 013). Here emerges the notion that enhancing people's access to information is the key to empowering them vis-à-vis the medical system (see also Balka, Rodje, & Bush, 2007). Sharing common scenarios where such access might be useful-such as when visiting multiple physicians or tracking one's fitness regime-this participant suggested that it could potentially enhance public health by helping providers make more specific recommendations to patients.…”
Section: In the Palm Of Your Hand: Empowering The Sexual Subjectmentioning
confidence: 99%
“……You smarten up and gain control" (Interviewee 013). Here emerges the notion that enhancing people's access to information is the key to empowering them vis-à-vis the medical system (see also Balka, Rodje, & Bush, 2007). Sharing common scenarios where such access might be useful-such as when visiting multiple physicians or tracking one's fitness regime-this participant suggested that it could potentially enhance public health by helping providers make more specific recommendations to patients.…”
Section: In the Palm Of Your Hand: Empowering The Sexual Subjectmentioning
confidence: 99%